Influence of elevated versus flat upper body position on objective snoring intensity: a case report - Verse, Thomas; Pirsig, Wolfgang; Maurer, Joachim T.; Hörmann, Karl; Stuck, Boris (Somnologie, 2004)
Subjective snoring intensity depends on body position. Unfortunately, there still is no accepted protocol for the objective assessment of snoring sounds. In general, objective data are lacking. This study objectively assessed the influence of the elevated versus the flat position of the upper body on the intensity of snoring. The snoring sounds of a 41-year-old male with primary snoring were recorded for 30 min during 54 consecutive nights in supine and in a slightly upright position with the upper part of the body being raised at a 15-degree angle. The tapes were evaluated by a technician who counted the immaculate snoring events. The number of snoring events was statistically significantly higher in the supine position as compared to the elevated body position (175.3±108.6 vs. 55.6±101.4). The authors conclude that the position of the upper part of the body may influence the severity of snoring.
Gesehen am 22.06.2022